Improvement of the calculation method of cyclone dust collectors - Ryzhov, Volodymyr (Technology audit and production reserves, 2019)
The object of research is a method for calculating the efficiency of cyclones using the magnitude of the velocity of transverse pulsations of a turbulent gas flow in the inlet of the cyclone. One of the most problematic issues when creating a new cyclonic technique for gas dust cleaning is the need to carry out a fairly large amount of work – modeling cyclones in laboratory conditions on model cyclones, taking into account the large-scale transition, etc. Therefore, the development of the most accurate analytical method for calculating the efficiency of cyclones is an important problem since it makes it possible to quickly and accurately determine all the necessary cyclone parameters for specific production conditions. During the study, patterns of dust particle deposition in the approximation of the «diffusion boundary layer» were used, which made it possible to calculate with high accuracy the efficiency of cleaning industrial dust in cyclones of various designs. At the same time, the time and the amount of experimental work are also significantly reduced in the development of new types of cyclones or in their modernization or selection. The most accurate dependencies are obtained for evaluating the most important parameters of dust cleaning efficiency in various cyclones. This is due to the fact that the method for calculating cyclones proposed in the work has a number of features, in particular, the development of new dependences for calculating the cut-off diameter «dh=50», the inertial capture coefficient of dust particles «E», and others. It is also proposed to use the average cross section the inlet pipe of the cyclone of the velocity of transverse pulsations of the turbulent gas flow and the new interpolation dependence of the coefficient of inertial capture of dust particles «E» at the potential flow regime in the inlet pipe of the cyclone x machines. Thanks to this, it is possible to obtain accurate values of the indicators of cleaning efficiency in cyclones of various design parameters. Compared with similar well-known calculation methods, this provides such advantages as accuracy of calculations, speed of execution and reliability of the results.